Studies on the Effect of Date of Fruit Collection on Seed Germination and Early Seedling Growth in Himalayan Ash (Fraxinus micrantha Lingelsh) - Singh, Virendra; Lavania, S. K.; Sah, V. K.; Kumar, Shashi (Indian Forester, 2005)
The present study was conducted to find out the optimum time of seed (fruit) collection in Fraxinus micrantha. The fruits were collected at fortnightly interval. The results of the present study revealed that the maximum germination of 44.50 per cent was found in treatment T3 (15th October collection or 180 days after anthesis) at a time when the fruit colour changed from green to grey orange. The moisture and dry weight/l00 seed at this stage was 17.82 per cent and 1.40 g, respectively. The shoot length, root length, shoot dry weight and root dry weight of 45 days old seedlings were also found better in this treatment. Therefore, the seeds of this species should be collected in the second fortnight of October (180 days after anthesis) at a time when the fruit colour changed to grey orange for better germination, seedling growth and vigour index.